Participant status through touch-in-interaction in a residential home for people with acquired brain injury - Raudaskoski, Pirkko (Social Interaction. Video-Based Studies of Human Sociality, 2020)
The focus of this paper is twofold. It first analyzes the types of touch-in-interaction in occupational therapy in an acquired brain injury residential home, and then looks more closely at the participant status of one specific resident in the context of the touches received and given. Touches are primarily initiated by staff members or researchers, and rarely by residents. In addition to those touches necessary for the practical help that the residents need in their care, touches are also part of greeting and leaving, getting attention, making requests or refusals, and commenting on or teasing others. Taps on the shoulder are considered firstly as a type of fleeting haptic sociality and, secondly, as a type of touch that only one of the residents seemed to be receiving. The taps the resident received suggest he is treated differently from the other residents and more like able-bodied participants. Therefore, his agency, his how-ability (vs. disability) in interactions, will be examined more closely in two examples. A close multimodal interaction analysis of the complexity of interactional situations reveals how the taps were accomplished as a lamination of the material, linguistic and embodied resources (the communicative resources of the resident and the embodied conduct made possible by the affordances of the setting) in the unfolding situation.